Serotonergic modulation of muscle acetylcholine receptors of different subunit composition. - García-Colunga, J (1996)
Modulation of muscle acetylcholine (AcCho) receptors (AcChoRs) by serotonin [5-hydroxytryptamine (5HT)] and other serotonergic compounds was studied in Xenopus laevis oocytes. Various combinations of alpha, beta, gamma, and delta subunit RNAs were injected into oocytes, and membrane currents elicited by AcCho were recorded under voltage clamp. Judging by the amplitudes of AcCho currents generated, the levels of functional receptor expression were: alpha beta gamma delta > alpha beta delta > alpha beta gamma > alpha gamma delta. The alpha beta gamma delta and alpha beta delta AcChoR Subtypes were strongly blocked by 5HT, whereas the alpha beta gamma receptor was blocked only slightly. The order of blocking potency of AcChoRs by 5HT was: alpha beta delta > alpha beta gamma delta > alpha beta gamma. 5HT receptor antagonists, such as methysergide and spiperone, were even more potent blockers of AcChoRs than 5HT but did not show much subunit selectivity. Blockage of alpha beta gamma delta and alpha beta delta receptors by 5HT was voltage-dependent, and the voltage dependence was abolished when the delta subunit was omitted. These findings may need to be taken into consideration when trying to elucidate the mode of action of many clinically important serotonergic compounds.